Minimasi Waste pada Proses Electroplating untuk Meningkatkan Efisiensi Proses dengan Menggunakan Metode Value Stream Mapping dan Perbaikan di PT MUI (Studi Kasus: Emblem H-Mark 115) - Hery Hamdi Azwir; Hirawati Oemar; Syafrina Yunita (President University, 2022)
MUI is a company that carries out the electroplating process for car accessories. With high demand, the efficiency process is very concerned because inefficiency can prolong the lead time process so that the production target is not achieved and will have an impact on the delivery of goods to customers. To minimize the factors that cause inefficiency, a value stream mapping method of lean manufacturing is used to identify waste. Two dominant wastes that affect efficiency based on the research results are waste defects and waste waiting. After that, analysis of the root cause of the problem was carried out and then repaired by the kaizen method. Improvements made in the form of maintenance of the water supply system, cleaning of transporter machines, modifying jig capacity to increase the quantity previously 90 pcs per batch to 144 pcs per batch. After repairs were made, the sigma level for the waste defect category increased by 0.42 from 3.35 to 3.77 and the total lead time decreased by 95,189 seconds from 164,886 seconds to 69,677 seconds, so as to increase the efficiency of the process cycle (PCE) by 6.74%.